Omega-3 Fatty Acid Profile of Eggs from Laying Hens Fed Diets Supplemented with Chia, Fish Oil, and Flaxseed - Coorey, R.; Novinda, A.; Williams, H.; Jayasena, Vijay (Blackwell Publishing Inc., 2015)
The aim of this study was to investigate the effect of diets supplemented with fish oil, flaxseed, and chia seed on the omega-3 fatty acid composition and sensory properties of hens' eggs. No significant difference in yolk fat content was found between treatments. The fatty acid composition of egg yolk was significantly affected by the dietary treatments. Inclusion of chia at 300 g/kg into the diet produced eggs with the highest concentration of omega-3 fatty acid. Eicosapentaenoic acid and docosahexaenoic acid were only detected in eggs from laying hens fed the diet supplemented with fish oil. Diet had a significant effect on color, flavor and overall acceptability of eggs. Types and levels of omega-3 fatty acids in feed influence the level of yolk omega-3 fatty acids in egg yolk. Inclusion of chia into the hens' diet significantly increased the concentration of yolk omega-3 fatty acid without significant change in sensory properties. Practical Application: Chia seeds are considered as one of the highest sources of omega-3 fatty acids among plants. By feeding hens diets that are enriched in omega-3 fatty acids, it is possible to increase omega-3 fatty acid content of the eggs. Such eggs could be a good source of omega-3 for human consumption.